Our lives with PKU: German patient voices - “Nothing about us without us” - Karin Lange; Jens Böhmer; Yvonne Deich; Daniel Dickneite; Pascale Fuchs; Verena Naunheim; Angelika Scholz; Christian Heimbold (Molecular Genetics and Metabolism Reports)
Objectives: Many publications describe experiences of healthcare professionals (HCPs) on managing phenylketonuria (PKU), but literature on the perspectives of individuals with PKU is limited. Nevertheless, patient insights and strategies to address challenges of living with PKU can provide guidance to HCPs and the PKU community to further optimise PKU care. Methods: A virtual meeting was held to elucidate the lived experience of patients with PKU and brainstorm best practice recommendations from the patient perspective. The meeting was moderated by a psychologist and attended by seven adults with PKU and one caregiver. Based on the outcomes of this meeting and subsequent online rating rounds, consensus statements (≥75 % agreement) reflecting patient focused considerations were developed using a modified Delphi approach. Results: Consensus was reached for 18 statements on five topics: the PKU diet, experience with HCPs throughout life, impact of PKU on everyday life, connecting with the PKU community, and future aspirations to facilitate life with PKU.To minimise the burden of diet, avoidance of hunger and offering new treatment options were identified, together with adequate education and support. Maintaining metabolic control throughout adulthood could be facilitated by easier access to clinics beyond in-person visits and by availability of treatment teams specifically equipped to provide PKU-adult care. To further support adults in reaching target blood Phe concentrations and personal goals, pegvaliase can be offered to those eligible. Finally, exchanging experiences with others from the PKU community through social media and live/virtual meetings may help individuals with PKU and caregivers to improve their knowledge and skills to manage PKU. Conclusion: These consensus statements provide unique insights on how challenges faced by individuals with PKU may be addressed and may provide guidance to HCPs as well as the PKU community and caregivers on ways to improve patient care and support.